811 Survey on health interview sheets for annual health checkups in japan. (24th April 2018) - Ando, Hajime; Ikegami, Kazunori; Sugano, Ryosuke; Michii, Satoshi; Shirasaka, Taiki; Ogami, Akira; Tadano, Tasuku
Abstract : Introduction: In Japan, all workers are required by law to receive annual health checkups. Annual health checkups are composed of health-based interviews (focused on subjective and objective complaints, anamnesis, and work history, for example), laboratory tests, chest X-rays, and ECG. Because interview sheets are not standardised, they are unique to each hospital. The aim of this study is to clarify the variety of interview sheets and to consider the issues surrounding them. Methods: We requested interview sheets from each hospital with cooperation from the National Federation of Industrial Health Organisation. We investigated the items that were asked in each sheet. Results: We received 70 interview sheets. Excluding six sheets because of duplication, we analysed 64 interview sheets. Sixty-two sheets asked about anamnesis (96.9%), 61 asked about subjective and objective complaints (95.3%), and 26 asked about work history (40.6%). There were no items that were asked on all interview sheets. There were 305 detailed items of anamnesis in total. Four sheets asked about working hours, three sheets asked about overtime hours, and six sheets asked about hazardous work. Discussion: Anamnesis, subjective and objective complaints, and work history are the items designated to interview sheets by law, but there were only a few sheets containing all these items. The purpose of annual health checkups is not only to detect diseases, but also to determine whether working environments are suitable for workers' health conditions. For this reason, these items are very important but most sheets do not include it. Subjective and objective complaints were asked for in most sheets, but details of it differed across sheets. Lifetime health management and comparisons of health checkup results are difficult because of non-standardised interview sheets. We suggest the standardisation of interview sheets in the future.